2020
DOI: 10.13057/biodiv/d211012
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity of eddoe and dasheen taro genotypes in response to saturated water and dryland cultivations

Abstract: Abstract. Hidayatullah CSR, Santosa E, Sopandie D, Hartono A. 2020. Phenotypic plasticity of eddoe and dasheen taro genotypes in response to saturated water and dryland cultivations. Biodiversitas 21: 4550-4557.  The phenotypic plasticity of dasheen and eddoe taro genotypes was evaluated based on growth and yield characters to select proper genotypes in response to climate change. The study was conducted at the Leuwikopo Experimental Farm, Bogor, Indonesia from May to October 2019. Dasheen (Talas Sutra and Tal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
2
0
5
Order By: Relevance
“…The genotypes which presented high PPI are more plastic and unstable and therefore can be selected for particular environments. Phenotypic plasticity among taro genotypes for nutritional traits has not been reported in literature, however, [22] Hidayatullah et al (2020) reported phenotypic plasticity for eddoe and dasheen taro for yield and yield components [23]. Tripodi et al (2020) reported plasticity among chilli pepper genotypes for health-related compounds in two environments [49].…”
Section: Phenotypic Plasticity and Stability Of The Genotypes For Nut...mentioning
confidence: 99%
See 1 more Smart Citation
“…The genotypes which presented high PPI are more plastic and unstable and therefore can be selected for particular environments. Phenotypic plasticity among taro genotypes for nutritional traits has not been reported in literature, however, [22] Hidayatullah et al (2020) reported phenotypic plasticity for eddoe and dasheen taro for yield and yield components [23]. Tripodi et al (2020) reported plasticity among chilli pepper genotypes for health-related compounds in two environments [49].…”
Section: Phenotypic Plasticity and Stability Of The Genotypes For Nut...mentioning
confidence: 99%
“…Nutritional composition of crops is highly influenced by genotype by environment interaction and therefore the genotypes generated should be evaluated under different environmental conditions to assess their phenotypic plasticity of environment. Phenotypic plasticity of a genotype is the extent to which their performance varies under different environmental conditions [20,21] (Bradshaw, 2006;Lande, 2009).Phenotypic plasticity evaluations are also important in the face of climatic change [22] (Hidayatullah et al, 2020). When the plasticity of a genotype for a particular trait near zero, the genotype is deemed stable and when it is far from zero, the genotype is plastic that is unstable [23] (Tripodi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Pada penelitian ini, yang dimaksud anakan adalah stolon atau umbi yang memiliki daun. Dari pandangan agronomi, keberadaan anakan merupakan karakter yang tidak diinginkan karena akan mengurangi alokasi fotosintat untuk pembentukan umbi (Santosa et al, 2004;Hidayatullah et al, 2020). Pada pemberian air setiap hari, genotipe S26 memiliki jumlah anakan 0.9, tertinggi dibandingkan dengan sembilan genotipe yang lain.…”
Section: Morfologi Tanamanunclassified
“…Upaya peningkatan produksi tersebut tidak mudah karena adanya fenomena perubahan iklim, yang sering berdampak pada musim kering yang lebih panjang. Di sisi lain, dampak keterbatasan kelembaban tanah terhadap pertumbuhan talas masih jarang diteliti (Suminarti, 2015;Hidayatullah et al, 2020). Menurut Suminarti (2015) tanaman talas yang diberi air irigasi setiap hari menghasilkan umbi yang lebih besar daripada yang disiram setiap 2 hari sekali.…”
unclassified
“…Berdasarkan bentuk umbinya, talas memiliki dua morfotipe yaitu eddoe (Colocasia esculenta var antiquorum) yang menghasilkan banyak umbi, dan dasheen (Colocasia esculenta var esculenta) yang menghasilkan umbi tunggal. Di Indonesia, jenis dasheen lebih umum dikenal sedangkan jenis eddoe merupakan introduksi baru (Hidayatullah et al, 2020a). Talas cukup menjanjikan untuk program diversifikasi pangan dan bagian talas yang dapat dimakan seperti umbi, daun, dan tangkai daun merupakan sumber karbohidrat, protein, serat makanan, mineral (kalsium, fosfor, magnesium dan zat besi) dan vitamin (Pitoyo et al, 2018).…”
unclassified